Copper-containing organic metal framework thin film material prepared by electrochemical direct oxidation method and preparation method and application of copper-containing organic metal framework thin film material

The copper-containing organometallic skeleton film materials are prepared under normal temperature and pressure by electrochemical direct oxidation, which solves the problems of high temperature and high pressure and by-products in traditional methods, and achieves the rapid preparation and industrial applicability of high-purity materials.

CN119663308APending Publication Date: 2025-03-21LUZHOU VOCATIONAL & TECHN COLLEGE +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411889350.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The preparation of traditional MOFs materials requires high temperature and high pressure, long reaction time, and easy to produce by-products or precipitate metal element, affecting the purity of the material and making it difficult to adapt to large-scale industrial production.

Method used

The electrochemical direct oxidation method is used to produce a copper-containing organometallic skeleton film material by performing constant voltage electrolysis at normal temperature and pressure, and reacting with copper chloride and tricarboxylic acid in the electrolyte solution.

Benefits of technology

It realizes the rapid preparation of high-purity copper-containing organometallic skeleton film materials under low energy consumption and mild reaction conditions, simplifies equipment and processes, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663308A_ABST
    Figure CN119663308A_ABST
Patent Text Reader

Abstract

The invention discloses a copper-containing organic metal framework thin film material prepared by an electrochemical direct oxidation method as well as a preparation method and application of the copper-containing organic metal framework thin film material, and belongs to the technical field of preparation of metal-organic framework materials. The preparation method comprises the following steps: dissolving cuprous chloride and trimesic acid in a solvent, and adding a deprotonation reagent to obtain an electrolyte; and performing constant-voltage electrolysis in an electrolyte by using a three-electrode system to obtain the copper-containing organic metal framework thin film material. According to the invention, an electrochemical direct oxidation method is applied to preparation of the copper-containing organic metal framework thin film material, no special requirement on a working electrode exists, and the single-phase copper-containing organic metal framework thin film material with high purity can be rapidly prepared within half an hour under the conditions of normal temperature and normal pressure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of metal-organic framework materials, and more specifically relates to a copper-containing organic metal framework film material prepared by an electrochemical direct oxidation method, and a preparation method and application thereof. Background Art

[0002] Metal-organic frameworks (MOFs), a class of crystalline three-dimensional porous nanomaterials assembled by organic ligands and metal ions or metal clusters through coordination bonds, have attracted widespread attention in the past two decades. Due to their extremely high specific surface area and diverse pore structures, MOFs have been widely used in many fields such as gas storage and separation, catalytic oxidation, biochemical sensing, and energy storage. In the field of catalysis, MOFs materials effectively integrate the advantages of homogeneous and heterogeneous catalysts, and have made remarkable progress in pollutant control, which is also the current research hotspot of MOFs material applications.

[0003] Traditionally, the synthesis of MOFs is mainly completed by hydrothermal or solvothermal methods. In this process, organic molecules, metal salts and templates are dissolved in water or organic solvents, and MOFs are prepared by heating at high temperature and high pressure for several hours to several days. These methods are relatively direct and have contributed to the discovery of a large number of materials. However, they usually involve high temperatures, reaching or even exceeding the boiling point of the reaction mixture solution; the synthesis is also usually carried out under high pressure, so the preparation of traditional MOFs materials often requires the use of customized reaction vessels. This has hindered the industrial scale-up production of MOFs. In addition, the commonly used solvent in MOFs synthesis is N,N-dimethylformamide (DMF), which tends to decompose rapidly at higher temperatures to produce byproducts including carbon monoxide, dimethylamine and formate. Some metal ions and organic ligands are prone to additional side reactions with these decomposition products, which brings difficulties to the preparation of MOFs and subsequent separation and purification. The decomposition of DMF also significantly hinders the recycling of solvents. These problems are more serious in the synthesis of metal-organic framework materials with high oxidation state metal cations. These high-valent metal ions are substitutionally inert and usually require the use of higher reaction temperatures or the addition of toxic and corrosive mineralizing additives (such as hydrofluoric acid) to obtain better finished products.

[0004] Compared with the traditional solvothermal method, electrochemical synthesis has begun to be used as a more convenient and greener chemical method in the synthesis of MOFs. In the electrochemical synthesis process, the reactivity of the metal central ion can be regulated by oxidizing or reducing the metal ion in the solution, thereby regulating its binding with the organic ligand linker to achieve the effect on the reaction yield, product particle size and morphology.

[0005] There are two methods for electrochemical synthesis of MOFs: direct synthesis and indirect synthesis.

[0006] Among the direct synthesis methods, the most typical one is the anodic dissolution of metal sources to synthesize MOFs, also known as the anodic dissolution method. In this process, the metal elements in MOFs are not provided by salts, but by anodic oxidation of metal electrodes in electrolytes containing organic ligands after power is applied. When an appropriate potential or current is applied, the metal working electrode is oxidized, and the released metal ions react with organic ligands to form MOFs near the electrode surface. During the anodic dissolution method, the rate of metal ion dissolution can be precisely controlled by constant potential or constant current, thereby controlling various MOFs properties, including particle size, crystal morphology, structure type, and in some cases adhesion to the electrode surface to promote film growth. However, since the substrate itself is both a powered electrode and a continuous process of power dissolution occurs during the anodic dissolution method to provide metal ions for MOFs, the substrate electrode for MOFs deposition is forced to be limited to a metal electrode. In addition, during this process, the substrate will inevitably be electrochemically corroded, resulting in the adhesion between MOFs and the substrate gradually decreasing as the growth preparation process proceeds.

[0007] The indirect synthesis method is mainly based on the reduction and deprotonation method at the cathode. In this process, the production of MOFs is also triggered by electrochemical reactions, but the specific implementation is through the synthesis of bases or their equivalents. For example, a study used high reduction potential to convert nitrates and water into nitrites and hydroxide ions, which are used to deprotonate terephthalic acid (H2BDC) and then react with Zn in the solution. 2+ The zinc-containing material MOF-5 was generated on the surface of a fluorine-doped tin oxide (FTO) electrode. This electrochemically mediated increase in pH provides potential applications for the preparation of a large number of MOFs and has additional advantages over the anodic dissolution method because it is compatible with a wider range of electrode materials, including inexpensive carbon electrodes, and surface-modified electrodes that promote the growth of MOFs films. However, since the reduction overpotential required for the reduction of nitrates is usually high, metal elements are often deposited together with MOFs during the preparation process, resulting in the formation of other byproducts and affecting the performance of MOFs.

[0008] Therefore, there is an urgent need in the art to develop a copper-containing organic metal skeleton thin film material with low energy consumption, mild reaction conditions, simple preparation method and required equipment, and high purity. Summary of the invention

[0009] The purpose of the present invention is to provide a copper-containing organic metal skeleton film material prepared by an electrochemical direct oxidation method, and a preparation method and application thereof, so as to solve the problems existing in the above-mentioned prior art that the reaction needs to be carried out under high temperature and high pressure, the required reaction time is long, which is not conducive to large-scale production; and it is easy to produce by-products or precipitate metal elements, affecting the purity of the organic metal skeleton film material.

[0010] To achieve the above object, the present invention provides the following solutions:

[0011] One of the technical solutions of the present invention is to provide a method for preparing a copper-containing organic metal framework thin film material by electrochemical direct oxidation, comprising the following steps:

[0012] Cuprous chloride and trimesic acid are dissolved in a solvent, and a deprotonating agent is added thereto to obtain an electrolyte; constant voltage electrolysis is performed in the electrolyte using a three-electrode system to obtain the copper-containing organic metal skeleton film material.

[0013] The invention uses trimesic acid as a ligand, dimethylformamide as an organic solvent and a ligand, and uses a deprotonating agent to achieve deprotonation of trimesic acid to prepare an electrolyte.

[0014] Preferably, the solvent comprises dimethylformamide and / or water; the deprotonating agent comprises 2,6-lutidine and / or sodium hydroxide; and the amount ratio of cuprous chloride, trimesic acid, deprotonating agent and solvent is 0.1-1.5 mmol:0.1-1.5 mmol:1 mmol:10 mL.

[0015] Preferably, in the three-electrode system, the working electrode comprises an ITO electrode, a graphite electrode, a glassy carbon electrode or a carbon paper electrode, the reference electrode comprises an Ag / AgCl electrode, and the counter electrode comprises a platinum electrode.

[0016] Preferably, the working electrode is surface modified before use to increase the adsorption of the prepared copper-containing organic metal framework film material to the electrode surface.

[0017] Preferably, the specific steps of the surface modification are: half immersing the ITO electrode in the mixed solution, using the ITO electrode as the working electrode and the Ag / AgCl electrode as the reference electrode, and performing surface modification on the ITO electrode by cyclic voltammetry.

[0018] Preferably, the semi-immersion means immersing the lower half of the ITO electrode in the mixed solution; the immersed part will have -COOH groups bonded to the electrode surface through covalent modification, and the unimmersed part is used to communicate with an external circuit.

[0019] Preferably, the preparation of the mixed solution comprises the following steps: firstly adding hydrochloric acid to the 4-aminobenzoic acid solution to adjust the acidity, then adding sodium nitrite, and mixing to obtain the mixed solution;

[0020] More preferably, the concentration of the 4-aminobenzoic acid solution is 0.5-1.5 mmol / L; the pH value after adjusting the acidity is <1; the sodium nitrite is in excess to complete the conversion of the amine substance to the diazonium salt; the mixing time is 5-10 minutes, and the purpose of mixing is to complete the conversion of the amine substance to the diazonium salt.

[0021] Preferably, the potential scanning range of the cyclic voltammetry is 0.6 to -0.5V.

[0022] Preferably, the temperature of the constant voltage electrolysis is room temperature, the pressure of the constant voltage electrolysis is normal pressure, the voltage of the constant voltage electrolysis is +0.5 to +0.75 V, and the time of the constant voltage electrolysis is 10 to 120 min.

[0023] The electrochemical direct oxidation method of the present invention can complete the preparation of copper-containing organic metal skeleton thin film materials in 30 minutes at room temperature and pressure, overcoming the requirements of high temperature, high pressure, long reaction time, and even special polytetrafluoroethylene hydrothermal reactor in the traditional solvent thermal synthesis method, and is more suitable for industrial transformation and application. At the same time, it avoids the problem that the working electrode of the anodic dissolution method needs to use a metal electrode, the substrate is prone to corrosion during the preparation process, and the adhesion between MOFs and the substrate (working electrode) gradually decreases as the growth preparation process proceeds, and the cathode reduction deprotonation method has the problem of metal element deposition and other by-products affecting the purity of the material.

[0024] The schematic diagram of the preparation process of the electrochemical direct oxidation method of the present invention is as follows Figure 1 As shown in the figure, the principle of the electrochemical direct oxidation method is: the monovalent metal ions (such as Cu + ) undergoes single electron oxidation to generate the corresponding divalent metal ion (Cu 2+ ). The in-situ generated Cu 2+ The ions will combine with the carboxylic acid organic ligand (trimesic acid) in the electrolyte, and finally a high-purity single-phase copper-containing organic metal skeleton thin film material will be quickly produced under normal temperature and pressure conditions.

[0025] The second technical solution of the present invention: provides a copper-containing organic metal skeleton thin film material prepared by the preparation method of the copper-containing organic metal skeleton thin film material prepared by the electrochemical direct oxidation method.

[0026] The third technical solution of the present invention is to provide the application of the copper-containing organic metal skeleton film material in the fields of gas adsorption separation, industrial catalysis, sensing application and analytical measurement.

[0027] The present invention discloses the following technical effects:

[0028] The present invention applies the electrochemical direct oxidation method to the preparation of copper-containing organic metal skeleton film materials, and obtains a three-dimensional network polymer material prepared by coordination reaction of copper ions and multi-dentate organic ligand trimesic acid. The material exhibits excellent performance in the fields of gas adsorption separation, industrial catalysis, sensor application, analytical measurement, etc.

[0029] The preparation method proposed in the present invention does not require the addition of additional metal salts, can be carried out at lower reaction temperatures and pressures, has low energy consumption, short reaction time, simple and controllable equipment, and has the characteristics of green chemistry. The electrochemical direct oxidation method has no additional requirements for the type of working electrode, avoids the restriction that copper electrodes must be used in the anodic electrolysis method, and enhances the adhesion of the film material to the electrode surface; at the same time, it also avoids the possibility of copper precipitation on the electrode surface in the cathode reduction method in principle, and thus it is easier to obtain a pure single-phase copper-containing organic metal skeleton film material. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 A schematic diagram of preparing a copper-containing organic metal framework thin film material by the electrochemical direct oxidation method, wherein HKUST-1 represents a copper-containing organic metal framework thin film material;

[0032] Figure 2 This is a cyclic voltammetry curve diagram when the ITO electrode is surface modified in Example 1;

[0033] Figure 3 This is a graph showing the relationship between current and time when the copper-containing organic metal framework thin film material is prepared by constant voltage electrolysis in Example 1;

[0034] Figure 4 It is a comparison diagram of the XRD spectrum of the copper-containing organic metal framework thin film material obtained in Example 1 and the XRD spectrum of the calculated simulation, wherein the black curve represents the XRD spectrum of the copper-containing organic metal framework thin film material obtained in Example 1, and the blue curve represents the XRD spectrum of the copper-containing organic metal framework thin film material calculated simulation;

[0035] Figure 5The XPS spectrum of the copper-containing organic metal skeleton thin film material obtained in Example 1, wherein a is the full XPS spectrum, b is the Cu 2p Energy spectrum of

[0036] Figure 6 This is the SEM image of the copper-containing organic metal framework thin film material obtained in Example 1. DETAILED DESCRIPTION

[0037] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0038] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0039] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0040] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0041] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0042] Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commercially available products.

[0043] Example 1

[0044] Working electrode surface modification:

[0045] Dissolve 4-aminobenzoic acid in ultrapure water to obtain a 1 mmol / L 4-aminobenzoic acid solution, add concentrated hydrochloric acid to adjust the acidity of the 4-aminobenzoic acid solution to a pH value of <1, then add excess sodium nitrite to it, stir the solution for 5 minutes to complete the conversion of amine substances to diazonium salts, and obtain a mixed solution; Place a clean 2×1 cm 2 The indium tin oxide (ITO) electrode was half immersed in the mixed solution (half-immersion means that the lower half of the ITO electrode was immersed in the mixed solution) to connect the circuit as the working electrode, and Ag / AgCl was used as the reference electrode. The surface of the working electrode was modified by cyclic voltammetry (potential scanning range of 0.6 to -0.5V). The surface modification electrical signal is as follows Figure 2 As shown, Figure 2 The surface modification process of the working electrode is verified by comparing it with the cyclic voltammetry process without sodium nitrite.

[0046] Preparation of copper-containing organic metal framework thin film materials:

[0047] 1mmol of cuprous chloride (CuCl) and 1mmol of trimesic acid were dissolved in 10mL of dimethylformamide, and 1mmol of 2,6-lutidine was added thereto as a deprotonating agent to obtain an electrolyte. The surface-modified ITO electrode was used as the working electrode, the Ag / AgCl electrode was used as the reference electrode, and the platinum electrode was used as the counter electrode. At room temperature and pressure, constant voltage electrolysis of +0.75V was performed in the electrolyte (the relationship between current and time during the electrolysis process is shown in the figure). Figure 3 As shown), after 30 minutes, the electrolysis is terminated due to the self-sealing phenomenon of the copper-containing organic metal skeleton film material on the electrode surface, thereby obtaining the copper-containing organic metal skeleton film material.

[0048] Performance characterization:

[0049] The ITO electrode after electrolysis was taken out from the electrolyte, rinsed with N,N-dimethylformamide and then characterized. The prepared copper-containing organic metal framework thin film material was characterized by X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and scanning tunneling microscopy.

[0050] The XRD spectrum of copper-containing organic metal framework thin film material is as follows Figure 4 shown. Figure 4 The figure is a comparison of the XRD spectrum of the copper-containing organic metal framework thin film material obtained in Example 1 and the XRD spectrum of the calculated simulation, wherein the black curve represents the XRD spectrum of the copper-containing organic metal framework thin film material obtained in Example 1, and the blue curve represents the XRD spectrum of the copper-containing organic metal framework thin film material calculated simulation. Figure 4It can be seen that by comparing with the computational simulation spectrum of the copper-containing organic metal skeleton thin film material, no obvious impurity phase signal was observed, indicating that the prepared copper-containing organic metal skeleton thin film material has a higher purity.

[0051] The XPS spectrum of copper-containing organic metal framework thin film material is as follows Figure 5 As shown, Figure 5 The XPS spectrum of the copper-containing organic metal skeleton thin film material obtained in Example 1, wherein a is the full XPS spectrum, b is the Cu 2p Energy spectrum of . Figure 5 It can be seen that the Cu, C, O signals in the material, the N signal from the deprotonation reagent and the In, Sn, O signals from the base material were detected, and no other impurity element peaks were observed. This also shows that the present invention synthesizes a single-phase copper-containing organic metal framework thin film material with high purity.

[0052] SEM images of copper-containing organic metal framework thin film materials Figure 6 As shown, Figure 6 This is a SEM image of the copper-containing organic metal framework thin film material obtained in Example 1. Figure 6 It can be seen that the prepared copper-containing organic metal skeleton thin film material has a typical octahedral structure and good crystallinity, which corresponds to the prominent XRD diffraction peaks.

[0053] Example 2

[0054] The difference from Example 1 is that the addition amounts of cuprous chloride and trimesic acid are adjusted to 0.1 mmol, and the rest are the same as Example 1.

[0055] Example 3

[0056] The difference from Example 1 is that the addition amounts of cuprous chloride and trimesic acid are adjusted to 0.5 mmol, and the rest are the same as Example 1.

[0057] Example 4

[0058] The difference from Example 1 is that the addition amounts of cuprous chloride and trimesic acid are adjusted to 1.5 mmol, and the rest are the same as Example 1.

[0059] Example 5

[0060] The difference from Example 1 is that the voltage of constant voltage electrolysis is adjusted to +0.5V, and the rest is the same as Example 1.

[0061] Example 6

[0062] The difference from Example 1 is that "dimethylformamide" is replaced by "water", and the rest is the same as Example 1.

[0063] Example 7

[0064] The difference from Example 1 is that "2,6-lutidine" is replaced by "sodium hydroxide", and the rest is the same as Example 1.

[0065] By verifying Examples 1 to 7, it can be seen that by changing the addition amounts of cuprous chloride and trimesic acid, no significant changes were observed in the crystallinity and purity of the prepared copper-containing organic metal skeleton thin film material; the obtained thin film material is not sensitive to the voltage value, solvent type and deprotonation agent type during the electrochemical preparation process, and the copper-containing organic metal skeleton thin film material can also be prepared with high selectivity by changing the solvent and the deprotonation agent type, which has great potential in industrial scale-up production; it is even possible to connect a household battery to the circuit as a power output to achieve the preparation of the copper-containing organic metal skeleton thin film material on the surfaces of multiple different electrodes (ITO electrode, graphite electrode, glassy carbon electrode or carbon paper electrode).

[0066] The copper-containing organic metal skeleton thin film material prepared by the present invention has a series of vacant Cu metal sites, and thus has broad application prospects in the fields of gas separation and adsorption, catalysis, sensing, etc. The new method proposed by the present invention can greatly simplify the preparation of the copper-containing organic metal skeleton thin film material, and can achieve precise control of the thickness of the copper-containing organic metal skeleton thin film material by controlling the electrolysis parameters.

[0067] Comparative Example 1

[0068] The copper-containing organic metal framework thin film material was prepared by the anodic dissolution method described in the article "On the electrochemical deposition of metal-organic frameworks, N. Campagnol, T. Van Assche, MY Li, L. Stappers, M. Dinca, JF M Denayer, K. Binnemans, DE De Vos and J. Fransaer, J. Mater. Chem. A, 2016, 4, 3914-3925."

[0069] Through verification, it is known that during the preparation process, Cu 2+ The ions are directly oxidized through the copper electrode, which has some restrictions on the electrode (it must be a copper electrode), and it is impossible to realize the preparation of the copper-containing organic metal skeleton film material on different electrodes such as ITO electrode, graphite electrode, glassy carbon electrode or carbon paper electrode as described in the present invention.

[0070] Comparative Example 2

[0071] The zinc-containing organic metal framework material was prepared by the cathode reduction deprotonation method described in the article "Electrochemical preparation of metal-organic framework films for fast detection of nitro explosives, WJ Li, SY Gao, QH Li and R Cao, J Mater Chem A, 2014, 2, 19473-19478."

[0072] Through verification, it is found that due to the application of a strong reduction voltage to achieve the generation of alkaline ions, the final prepared film, in addition to the organic metal framework material, inevitably contains products generated by the reduction of metallic zinc, and it is impossible to efficiently and universally prepare organic metal framework materials containing highly reducing metals.

[0073] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0074] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a copper-containing organic metal framework thin film material by electrochemical direct oxidation, characterized in that: The steps include: Cuprous chloride and trimesic acid are dissolved in a solvent, and a deprotonating agent is added thereto to obtain an electrolyte; constant voltage electrolysis is performed in the electrolyte using a three-electrode system to obtain the copper-containing organic metal skeleton film material.

2. The method according to claim 1, characterized in that The solvent includes dimethylformamide and / or water; the deprotonating agent includes 2,6-lutidine and / or sodium hydroxide; the amount ratio of cuprous chloride, trimesic acid, deprotonating agent and solvent is 0.1-1.5 mmol: 0.1-1.5 mmol: 1 mmol: 10 mL.

3. The method according to claim 1, characterized in that In the three-electrode system, the working electrode includes an ITO electrode, a graphite electrode, a glassy carbon electrode or a carbon paper electrode, the reference electrode includes an Ag / AgCl electrode, and the counter electrode includes a platinum electrode.

4. The method according to claim 1, characterized in that: The working electrode is surface modified before use.

5. The method according to claim 4, characterized in that The specific steps of the surface modification are: half immersing the ITO electrode in the mixed solution, using the ITO electrode as the working electrode and the Ag / AgCl electrode as the reference electrode, and performing surface modification on the ITO electrode by cyclic voltammetry.

6. The method according to claim 5, characterized in that The preparation of the mixed solution comprises the following steps: firstly adding hydrochloric acid to the 4-aminobenzoic acid solution to adjust the acidity, then adding sodium nitrite, and mixing to obtain the mixed solution; The concentration of the 4-aminobenzoic acid solution is 0.5-1.5 mmol / L; the pH value after adjusting the acidity is <1.

7. The method according to claim 5, characterized in that The potential scanning range of the cyclic voltammetry is 0.6 to -0.5V.

8. The method according to claim 1, characterized in that The voltage of the constant voltage electrolysis is +0.5 to +0.75 V, and the time of the constant voltage electrolysis is 10 to 120 minutes.

9. The copper-containing organic metal framework thin film material prepared by the method according to any one of claims 1 to 8.

10. Use of the copper-containing organic metal framework thin film material according to claim 9 in the fields of gas adsorption separation, industrial catalysis, sensing application and analytical measurement.